Art as a verb: The Evolving Continuum : Installations, Performances and Videos by 13 African-American Artists - King-Hammond, Leslie; Stokes Sims, Lowery; Maryland Institute, College of Art, Baltimore (Baltimore : Maryland Institute, College of Art, 1988)
Abramson, Charles ; Hammons, David ; Hassinger, Maren ; Hill, Candace ; Jackson-Jarvis, Martha ; Nengudi, Senga ; O'Grady, Lorraine ; Pindell, Howardena ; Peper, Adrian ; Ringgold, Faith ; Saar, Betye ; Scott, Joyce ; Sullivan, Kaylynn
Art as a Verb: The Evolving Continuum : Installations, Performances and Videos by 13 African-American Artists, Maryland Institute, College of Art and funded by the National Endowment for the Arts, the Metropolitan Life Foundation, the Maryland State Arts Council, and the Robert and Jane Meyerhoff Special Programs Endowment, Maryland Institute, College of Art, Baltimore, November 21, 1988 - January 8, 1989
boek